WYBRANE ASPEKTY PRAWNE W ‘HISTORIA AUGUSTA’ - Bogacz, Ludomir (Zeszyty Prawnicze, 2017)
Private Law in the ‘Augustan History’ Summary The author of Historia Augusta (The Augustan History) had some knowledge of the law. He knew, for instance, that the emperor had to issue his consent for an act of adrogation to be valid, but failed to describe its procedure correctly. He knew that the lex Fufia Caninia limited manumission to a maximum of one hundred slaves, but he did not know that this law was applicable only to testamentary manumissions. The biographer displayed his knowledge but distorted and fabricated history. However, as his acquaintance with the law was limited and pertained to the law in force at a much later period, it was wrong on the particulars in force earlier. In-depth analysis of the Historia Augusta with reference to Roman law may be helpful in telling fact from fiction in this extraordinary work.